THE BOARD OF DIRECTORS' RESPONSIBILITY FOR SHAREHOLDER LOSSES IN BUYBACK POLICIES: AN ANALYSIS OF COURT DECISIONS AND CORPORATE PRACTICES - Lenny Mutiara Ambarita; Muldri Pudamo James Pasaribu (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the fiduciary duty of directors in buyback policies, the consistency of their application in court decisions, and the effectiveness of OJK supervision in protecting shareholders. The method used is normative legal research with statutory, conceptual, case, and comparative approaches. Primary legal materials include the Company Law (UUPT), the Capital Market Law, the POJK (OJK Regulation), and court decisions; secondary legal materials include academic literature; and tertiary legal materials include legal dictionaries and encyclopedias. The analysis was conducted qualitatively and normatively by examining the consistency between legal norms, doctrine, and judicial practice. The results indicate that a gap remains between norms and practice. Some issuers implement buybacks in accordance with regulations, but others exploit regulatory relaxations to circumvent the GMS mechanism, thereby weakening the position of minority shareholders. Court decisions, such as Supreme Court No. 280 K/Pdt/2012 and Supreme Court No. 2826 K/Pdt/2021, demonstrate inconsistencies in the application of fiduciary duty and the business judgment rule. The phenomenon of nominee directors further strengthens the potential for conflicts of interest in buyback implementation. Meanwhile, OJK supervision is still considered weak because the sanctions imposed have not had a deterrent effect.